Development time mediates the effect of larval diet on ageing and mating success of male antler flies in the wild. Issue 1938 (11th November 2020) - Angell, Christopher S.; Oudin, Mathieu J.; Rode, Nicolas O.; Mautz, Brian S.; Bonduriansky, Russell; Rundle, Howard D.
Abstract : High-quality developmental environments often improve individual performance into adulthood, but allocating toward early life traits, such as growth, development rate and reproduction, may lead to trade-offs with late-life performance. It is, therefore, uncertain how a rich developmental environment will affect the ageing process (senescence), particularly in wild insects. To investigate the effects of early life environmental quality on insect life-history traits, including senescence, we reared larval antler flies ( Protopiophila litigata ) on four diets of varying nutrient concentration, then recorded survival and mating success of adult males released in the wild. Declining diet quality was associated with slower development, but had no effect on other life-history traits once development time was accounted for. Fast-developing males were larger and lived longer, but experienced more rapid senescence in survival and lower average mating rate compared to slow developers. Ultimately, larval diet, development time and body size did not predict lifetime mating success. Thus, a rich environment led to a mixture of apparent benefits and costs, mediated by development time. Our results indicate that 'silver spoon' effects can be complex and that development time mediates the response of adult life-history traits to early life environmental quality.